Pengaruh Model Pembelajaran Kooperatif Tipe STAD Terhadap Hasil Belajar Kognitif Bahasa Madura Kelas IV SDN Tengket 1 - Nisa', Mutiatun; Mardiyana, Isna Ida (JOURNAL OF EDUCATION FOR ALL, 2024)
The purpose of this research is to look at the use of the student team achievement division (STAD) type cooperative learning model as an effort to improve learning outcomes in Madurese language subjects, namely "to determine the influence of the student team achievement division (STAD) type cooperative learning model on Madura language cognitive learning outcomes class IV at SDN Tengket 1. Based on the results of the Mann Whitney pretest, it shows that the sig (2-tailed) value is <0.5, namely 0.245. In accordance with the test criteria, if the sig (2-tailed) value is <0.5 then there is a difference or Ho is rejected and Ha is accepted so that there is a difference between the experimental class and control class questions. Meanwhile, the posttest value shows that the sig (2-tailed) value is <0.5, namely 0.011. In accordance with the testing criteria, if the sig (2-tailed) value is <0.5 then there is a difference or Ho is rejected and Ha is accepted. Therefore it can be concluded that the Student Team Achievement Devision (STAD) type cooperative learning model has a quite significant effect on learning outcomes.